The Library - Stewart, Sarah; Pictures by David Small (London Frances Lincoln Children Books, 1995)
Elizabeth Brown loves to read more than anything else, but when her collection of books grows and grows, she must make a change in her life.
Include Color illustrations
Keywords: Libraries -- Rhymes